Social Aspects of Transnational Corporations' Activities in the New EU Member States; Społeczne aspekty działalnosći korporacji transnarodowych w nowych krajach członkowskich Unii Europejskiej - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2012)
Water resources are among the most valuable resources of the natural environment. The sustainable and integrated management of these resources is the basis of European water policy. Pursuant to the Water Framework Directive, all waters in the European Union should achieve a state considered at least good by the year 2015. Just how this objective can be met continues to be a topic of discussions in some of the Member States. There exist serious problems and delays in performing and implementing the provisions of the Directive in most EU countries. What is more, the state of the water economy in several countries, including Poland, has been criticized by the European Commission. Many challenges stand before European water policy. They require solutions on a global and local level. This article presents current key problems and planned directions for EU water policy development, subjected to analysis and assessment. Note is taken on the newest initiative of the European Commission in the area of water policy, especially the plan for protecting Europe's water resources-the Blueprint to Safeguard Europe's Water Resources – – Celem artykułu jest zbadanie głoẃnych społecznych aspektoẃ zwiazanych ~z działalnosćia korporacji transnarodowych w nowych krajach członkowskich Unii Europejskiej (UE) oraz prob́a odpowiedzi na pytanie, czy korporacje transnarodowe moga pomoć złagodzicśpołeczne problemy wystepujace w krajach goszczacych, czy tezṡa zŕod́łem dodatkowej nieroẃnowagi w sferze społecznej. Analiza i ocena skali zaangazȯwania korporacji transnarodowych w nowych krajach członkowskich UE została przeprowadzona z wykorzystaniem bazy danych UNCTAD, OECD i CEIC. Analiza empiryczna obejmuje cztery kraje, tj. Czechy, Wegry, Polske i Słowacje. Wyniki badanẃskazuja, zė korporacje transnarodowe moga odgrywacṕozytywna role w łagodzeniu społecznych problemoẃ w krajach goszczacych, ktoŕymi sa bezrobocie, ubośtwo i społeczne wykluczenie. Korporacje transnarodowe tworza i utrzymuja stosunkowo duzȧ liczbe miejsc pracy w nowych krajach członkowskich UE, oferujac wyzṡze wynagrodzenie pracownikom, nizḟirmy miejscowe. Ich skłonnosćd́o koncentracji bezposŕednich inwestycji zagranicznych w rozwinietych regionach ma jednak niejednoznaczny wpływ na spoj́nosćśpołeczno-ekonomiczna poszerzonej UE, badanej na poziomie regionalnym. Korporacje transnarodowe wydaja sie stymulowacńieroẃnosći na poziomie miedzyregionalnym i wewnatrz regionoẃ. Jednoczesńie korporacje te sa liderami społecznej odpowiedzialnosći w nowych krajach członkowskich UE.
Keywords: 330